Socio-Intellectual Construction of Mandailing Clerics in the 20th Century and Their Contributions - Ikbal, Muhammad; Nasution, Suryadi; Hanida, Rahmi Seri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Ulama play a crucial role as agents of social control through their knowledge and leadership in society. In the Mandailing region, the presence of Ulama is significant and has contributed meaningfully to the development of Islamic scholarship in the archipelago. Among them, three prominent figures, Shaykh Abdul Halim Khatib, Shaykh Syihabuddin, and Shaykh Abdul Qadir Bin Shabir, stand out with intellectual capacities comparable to other renowned Nusantara Ulama. This study aims to analyze their scientific networks and intellectual social constructions. Using a qualitative approach and library research methods, including documentation and content analysis, the research explores the underlying patterns of their scholarly engagement. Findings show that Mandailing Ulama focuses more on community movements than written scholarship. This is largely because the local society values Ulama as religious scholars and traditional and social leaders. Their active involvement in communal life limits the time and opportunity for writing. Nonetheless, the intellectual focus of these three Ulama centers on fundamental Islamic theology, particularly the 20 attributes of Allah (sifat 20). Shaykh Syihabuddin is especially noted for his contribution to the Naqshbandiyyah Sufi order, which he elaborates in his book Fath al-Qalb. This work extends beyond theoretical insights into practical spirituality. Similarly, Shaykh Abdul Halim Khatib was deeply engaged in Sufi practice and reportedly taught such knowledge at the Mustafawiyah Pesantren. The three Ulama exemplify a blend of spiritual leadership and theological scholarship rooted in the Mandailing context.